All‐Printed Flexible Hygro‐Thermoelectric Paper Generator. Issue 9 (22nd January 2023) - Shen, Haoyu; Xu, Ke; Duan, Yulong; Wu, Peilin; Qian, Zhiyun; Chen, Yonghao; Luo, Yao; Liu, Chaocheng; Li, Yang; Cui, Jiedong; Liu, Detao
Abstract: The conversion of ubiquitous hygrothermal resources into renewable energy offers significant potential for cable‐free, self‐powered systems that can operate worldwide without regard to climatic or geographic limitations. Here, an all‐printed flexible hygro‐thermoelectric paper generator is demonstrated that uses bifunctional mobile ions and electrons to make the moist‐diffusion effect, the Soret effect, and the Seebeck effect work synergistically. In the ordinary hygrothermal settings, it generates an unconventional hygro‐thermoelectric output pattern and shows almost a dozen‐fold increase in positive hygro‐thermopower of 26.70 mV K −1 and also another negative hygro‐thermopower of −15.71 mV K −1 compared to pure thermopower. A single paper generator can produce a giant 680 mV displaying typical cyclic sinusoidal waveform characters with volt‐sized amplitudes. The ion‐electron conductive ink is easily printable and consists primarily of a Bi2 Te3 /PEDOT:PSS thermoelectric matrix modulated with a hygroscopic glycerol that releases ion charges for moist‐diffusion effect and Soret effect, as well as electron charges for Seebeck effect. The emerged hygro‐thermoelectric harvesting strategy from surrounding hygrothermal resources offers a revolutionary approach to the next generation of hybrid energy with cost‐efficiency, flexibility, and sustainability, and also enables large‐scale roll‐to‐roll production. Abstract : A conversion of ubiquitous hygrothermal resources into renewable energy offers significant potentials for cable‐free, self‐powered systems that operates globally without climate or geography limitations. The all‐printed hygro‐thermoelectric paper generator is reported to make moist‐diffusion effect, Soret effect, and Seebeck effect work synergistically for harvesting giant power, proposing a revolutionary approach to collect useful renewable energy from ambient hygrothermal resources.